2016
DOI: 10.1002/bdm.1995
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Variations in Reasons for Advice Seeking

Abstract: Five studies examined cultural differences in reasons for advice‐seeking behaviors. Content analyses in Study 1A and self‐ratings in Study 1B consistently revealed that Euro‐Canadians were more likely than East Asians (mainly Chinese) to seek advice for informational reasons, whereas East Asians were more likely than Euro‐Canadians to seek advice for relational reasons. Study 2A showed that Chinese displayed a higher level of relationship concern than Euro‐Canadians in deciding from whom to seek advice in a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…For example, compared to less collectivistic European-Americans, Russian residents tend to give more advice and solicit advice, and view advice-giving as an expression of social support (Chentsova-Dutton & Vaughn, 2012). Chinese people engage in advice-seeking behaviour to enhance their relationships more than European-Canadians (Ji et al, 2017) and are more likely than Americans to believe that solicited advice brings good outcomes to distressed individuals, including confidence, decreased stress, and fast recovery from personal hardships (Feng, 2015).…”
Section: Advice In Collectivismmentioning
confidence: 99%
“…For example, compared to less collectivistic European-Americans, Russian residents tend to give more advice and solicit advice, and view advice-giving as an expression of social support (Chentsova-Dutton & Vaughn, 2012). Chinese people engage in advice-seeking behaviour to enhance their relationships more than European-Canadians (Ji et al, 2017) and are more likely than Americans to believe that solicited advice brings good outcomes to distressed individuals, including confidence, decreased stress, and fast recovery from personal hardships (Feng, 2015).…”
Section: Advice In Collectivismmentioning
confidence: 99%
“…These studies focused predominantly on the European (Chentsova-Dutton & Vaughn, 2012), American (Glide, 2015), Asian (Morrow, 2012), and the African (Hampel, 2015) regions. Similarly, cross-cultural comparison studies on advice strategies also centered on only a few cultures, for instance comparing the Russian and American cultures (Chentsova-Dutton & Vaughn, 2012), the American and Chinese cultures (Feng, 2015;Feng & Feng, 2011), and the East Asian and the Euro-Canadian cultures (Ji et al, 2016). Therefore, not much is known about the advice strategies of other cultural communities.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the primary sampling concerns have been discussed in the "Empathic Decision-Making and Individual Differences" section (pg 76). There is strong evidence that "good" helping is culturally defined (Chentsova-Dutton & Vaughn, 2012;Ji et al, 2017;Mojaverian & Kim, 2013), and as such, the results of this study can only be generalized within a highly educated, Midwestern, and predominantly Caucasian setting. If this study was conducted in more diverse populations or other countries, different helping strategies might be considered effective and ineffective.…”
Section: Limitationsmentioning
confidence: 84%
“…The next finding in this experiment suggested that empathic decision -making cannot be predicted by demographic or personality variables. Prior studies have suggested that gender (Smith, 2006;Cristov-Moore et al, 2014;Eisenberg & Lennon, 1983;Rose & Rudolph, 2006;Oswald, 2000;Eagly & Crowley, 1986), culture (Chentsova-Dutton & Vaughn, 2012;Ji et al, 2017;Mojaverian & Kim, 2013), personality (Cavallo et al, 2016), and attachment style (Harel et al, 2011) Personality results were also interesting since empathic decision-making did not seem to be influenced by interpersonal patterns, related personality traits, or attachment style. These results do not support established literature.…”
Section: Empathic Decision-making and Individual Differencesmentioning
confidence: 93%
See 1 more Smart Citation